2021
DOI: 10.1021/acsmacrolett.1c00356
|View full text |Cite
|
Sign up to set email alerts
|

Light-Enabled Reversible Shape Transformation of Block Copolymer Particles

Abstract: Confined self-assembly of block copolymers (BCPs) is effective to manipulate various shapes of particles. In emulsion confined self-assembly, reversibly light-trigged switchable BCP particles are extremely expected, yet rarely reported. Herein, a novel strategy is developed to realize reversibly light-responsive shape-transformation of BCP particles by constructing functional surfactants with light-active azobenzene (azo) groups in the confined self-assembly of BCPs within emulsion droplet. Ultraviolet and vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 47 publications
1
54
0
Order By: Relevance
“…The shape transformation of polymeric nanostructures also attracts much attention of scientists, which can change their rheological, optical and physiological properties, [4][5][6] DOI: 10.1002/marc.202200131 facilitating the exploitation of their potentials in diverse applications, including drug delivery, [7] catalysis, [8] antimicrobial, [9,10] imaging, [11] and so forth. Typically, external stimuli such as light, [12][13][14] temperature, [15,16] pH, [17][18][19] and redox [20] are used to trigger the shape transformation of stimuli-responsive polymeric nanostructures. [21] Comparing with other stimuli, light is a non-interventional stimulus and widely used to trigger the morphology and structure transformation, while maintains the physicochemical environment unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…The shape transformation of polymeric nanostructures also attracts much attention of scientists, which can change their rheological, optical and physiological properties, [4][5][6] DOI: 10.1002/marc.202200131 facilitating the exploitation of their potentials in diverse applications, including drug delivery, [7] catalysis, [8] antimicrobial, [9,10] imaging, [11] and so forth. Typically, external stimuli such as light, [12][13][14] temperature, [15,16] pH, [17][18][19] and redox [20] are used to trigger the shape transformation of stimuli-responsive polymeric nanostructures. [21] Comparing with other stimuli, light is a non-interventional stimulus and widely used to trigger the morphology and structure transformation, while maintains the physicochemical environment unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…However, the wider application of emulsion confinement self-assembly, especially in large-scale production, is still limited by the tedious chemical synthesis of involved block copolymers. In addition, although there are plenty of published works dealing with the morphology modulation of polymeric microparticles by tuning block copolymer backbones structures, surfactants compositions, and concentrations ( Deng et al, 2016 ; Shin et al, 2018 ; Ku et al, 2019 ; Hu et al, 2021 ; Xu et al, 2021 ), the research work involving the post-modification and further application of these polymeric microparticles is still quite limited.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, azobenzene-based photoswitches are excellent candidates for developing reversible light-responsive particles. , Upon irradiation, azobenzene undergoes a photoisomerization process between its nonpolar trans- and polar cis- configurations according to the specific wavelength of light. , In addition, most azobenzene-containing molecules are highly stable during their reversible photoswitching cycles relative to other light-responsive moieties, , making them promising to achieve robust and reproducible shape-changing BCP particles. As an example, Zhu et al recently reported an excellent work using azobenzene-based organic molecules for achieving light-responsive BCP particles …”
Section: Introductionmentioning
confidence: 99%
“…As an example, Zhu et al recently reported an excellent work using azobenzene-based organic molecules for achieving light-responsive BCP particles. 36 Developing photoswitchable inorganic nanoparticles (NPs) in combination with azobenzene can provide additional important benefits for producing shape-changing BCP particles. Importantly, the structural complexity of BCPs can be exploited to confine NPs into desired locations, enhancing or suppressing the expression of the distinct physical properties of inorganic NPs through spatially controlled interactions with other constituents.…”
Section: ■ Introductionmentioning
confidence: 99%